Parent–Child Closeness and Parents’ Meaning in Life in Personal Meaning in Life: Examining Ethnic Differences - Yu, Elizabeth A.; Chang, Edward C. (The Family journal (Alexandria, Va.), 2018)
We examined for ethnic differences in how parent–child closeness and parents’ meaning in life predict personal meaning in life between 187 Asian American and 201 European American college students. Results indicated that parent–child closeness predicted a significant amount of variance in personal meaning in life for both groups. Furthermore, parents’ meaning in life added a significant amount of variance, above and beyond parent–child closeness, in predicting personal meaning in life for Asian Americans, but not for European Americans. Our findings indicate that although parents play some role in contributing to college-aged individuals’ meaning in life, there are still important ethnocultural nuances to consider. Findings from the present study provide a foundation for further research to continue examining the role of parents and familial relationships in meaning in life and other well-being outcomes. Further discussion of the study’s findings and implications are discussed.